2019
DOI: 10.1177/0967033519837986
|View full text |Cite
|
Sign up to set email alerts
|

Classification of affect using deep learning on brain blood flow data

Abstract: We present a convolutional neural network-and long short-term memory-based method to classify the valence level of a computer user based on functional near infrared spectroscopy data. Convolutional neural networks are well suited for capturing the spatial characteristics of functional near infrared spectroscopy data. And long short-term memories are demonstrated to be good at learning temporal patterns of unknown length in time series data. We explore these methods in a combined layered architecture in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…EEG and fNIRS data have also been used in studying both within-subject [8] and cross-subject [9] classification scenarios. The authors have identified neural correlates of emotions using fNIRS data across subjects.…”
Section: Crowdsourcing Annotationsmentioning
confidence: 99%
“…EEG and fNIRS data have also been used in studying both within-subject [8] and cross-subject [9] classification scenarios. The authors have identified neural correlates of emotions using fNIRS data across subjects.…”
Section: Crowdsourcing Annotationsmentioning
confidence: 99%
“…Some studies have analyzed the cortical activations of subjects to predict emotions. Bandara et al 86 used music videos from the DEAP database 99 to classify the emotional valence and arousal of subjects using a CNN +LSTM architecture and fNIRS data recorded from the prefrontal cortex. Using the subjects' self-assessments as ground-truth, a classification accuracy of 77% was reported.…”
Section: Analysis Of Cortical Activationsmentioning
confidence: 99%
“…Another use of fNIRS is in psychological studies. Bandara et al [261] reported a CNN with Long Short Term Memory (LSTM) to analyze spatiotemporal oxy‐ and deoxy‐ hemodynamics data from the prefrontal cortex for classifying human emotions and achieved 77% accuracy using both oxy‐ and deoxy‐hemoglobin data and 1‐second time steps. These results demonstrate that spatiotemporal features are desired for fNIRS‐based classification tasks, and the DL methods excel in feature exaction in such high dimensional data sets.…”
Section: Applications In Biomedical Opticsmentioning
confidence: 99%